Membangun Media Promosi Sparepart Mobil Berbasis Web Dengan Fitur Augmented Reality - Latifah, Ayu; Al ZIdane Putra Fedy, Mahesa (Institut Teknologi Garut, 2025)
The use of Augmented Reality (AR) technology is growing as an innovative solution for product promotion in the digital age. This study aims to develop a web-based promotional medium for car spare parts with AR features at the Alfa Jaya Wheels store, in order to increase marketing effectiveness and make it easier for consumers to recognize products such as wheels, tires, and bolts without having to come directly to the store. The application was designed and developed using the Multimedia Development Life Cycle (MDLC) method, which includes the stages of concept, design, material collection, assembly, testing, and distribution. The results of the study show that the application is capable of displaying 3D models of spare parts interactively and in real-time, thereby supporting the consumer decision-making process. The implementation of web-based AR has been proven to increase the visual appeal of promotions, expand market reach, and add value to the marketing strategy of spare parts stores in the digital era.